The Impact of Reading Fluency on College Performance - Bessie, Yoseph Ricardo; Rahayu, Gupuh - (International Research-Based Education Journal, 2023)
Reading fluency is an essential skill for academic achievement. Fluent readers are able to swiftly and accurately comprehend written information, allowing them to focus on the meaning and implications of what they are reading. This paper investigates the relationship between reading fluency and academic outcomes, including reading comprehension, writing and vocabulary. The study seeks to examine the nature of this relationship, how reading fluency influences specific areas of academic achievements, and whether individual differences, such as age or reading aptitude, moderate this relationship. Fifteen students from the fourth semester of the English Department at Universitas Nusa Cendana were recruited for this study, and a longitudinal design was used to investigate the relationship between reading fluency and academic achievement. The results indicate that reading fluency is positively related to reading comprehension, writing and vocabulary knowledge. Individual differences in age and reading aptitude also appear to mitigate the relationship between reading fluency and academic achievement.